Business Development Design Using the Business Model Canvas (BMC) Approach and Swot Analysis for One Alumni Coffee Pekan Baru - Tengku Firli Musfar; Dian Pratiwi; Meilisa; Rio Fandy Sitepu; Endang Ropika T (Jurnal Multidisiplin Madani, 2022)
This study designs business development using the Business Model Canvas approach and SWOT analysis. This study determined the Business Model Canvas elements that need to be improved, so that Business Model Canvas improvements can be made in business development. The approach used in this research is descriptive qualitative by providing an explanation of the company's situation. The stages carried out are tabulating the results of interviews related to the 9 Business Model Canvas components, filling in the tabulation results in the columns of the 9 Business Model Canvas components with the help of the BMC Pro application, conducting a SWOT analysis based on the tabulation results of the 9 Business Model Canvas components, and compiling an improved Business Model Canvas based on the results of the SWOT matrix. The results of this study are that the One Alumni Coffee business model has been compiled in its current condition using the Business Model Canvas approach, the Business Model Canvas One Alumni Coffee elements that need to be improved are identified in all (9 blocks) of the Business Model Canvas, and strategies and improvement programs that can be made from the results of BMC improvements in the development of the One Alumni Coffee business after using SWOT analysis